2020
DOI: 10.3390/met11010064
|View full text |Cite
|
Sign up to set email alerts
|

Holding Time Influence on the Hot Ductility Behavior of a Continuously Cast Low Alloy Steel

Abstract: Cracking during the continuous casting process is undesirable and continuous work is being carried out to find further improvements and understand the mechanisms that lead to failure. Investigations on the hot ductility behavior of a continuously cast low alloyed steel using different holding times before straining were done in the present work. Samples were heated to melting temperature in a vacuum atmosphere and then cooled to one of the three test temperatures chosen: 750, 850, and 900 °C. When the desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Curves are shown in Figure 1. The results for the steel number 1, which have been partially published [8], show a ductility minimum between 850 and 700 °C, which is determined by the reference value of 40%, indicated. As for the steel number 2, the ductility seen is higher at all points, with its lowest at 700 °C and no clear ductility trough formed, never reaching the minimum of 40 % of reduction of area.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Curves are shown in Figure 1. The results for the steel number 1, which have been partially published [8], show a ductility minimum between 850 and 700 °C, which is determined by the reference value of 40%, indicated. As for the steel number 2, the ductility seen is higher at all points, with its lowest at 700 °C and no clear ductility trough formed, never reaching the minimum of 40 % of reduction of area.…”
Section: Resultsmentioning
confidence: 86%
“…The steel number 2 has more alloying elements, such as B, Cr, Ni and Ti, and also both lower sulfur content and more vanadium. The samples were machined with equal geometry for both steels, in dog-bone shape and axis parallel to the rolling directions, as shown in previous work [8]. Experiments were performed in an in-house built thermomechanical simulator, the BETA 250-5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in Table 2 and Figure 11 , the particles with sizes within 3.01–4.00 μm represents the biggest volume, followed by particles with size within 2.01–3.00 μm, 4.01–5.00 μm, 5.01–10.00 μm, and 1.00–2.00 μm and greater than 10 μm. Considering several types of research on fracture surfaces, there is clear evidence that poor hot ductility of investigated steels was associated with the presence of AlN and/or AlN-MnS particles [ 10 , 11 , 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Precipitation kinetics simulations performed by the authors of [ 29 ] showed that longer holding time leads to growth of AlN at grain boundaries, a coarsening of MnS at dislocations, and a coarsening and growth of AlN at MnS.…”
Section: Discussionmentioning
confidence: 99%
“…Considering several types of research on fracture surfaces, there is clear evidence that poor hot ductility of investigated steels was associated with the presence of AlN and/or AlN-MnS particles [ 10 , 11 , 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Precipitation kinetics simulations performed by the authors of [ 29 ] showed that longer holding time leads to growth of AlN at grain boundaries, a coarsening of MnS at dislocations, and a coarsening and growth of AlN at MnS. The authors of [ 31 ] found that in FeCrAl steel, the number of AlN particles increases with increasing cooling rate, although the volume fraction is relatively unaffected.…”
Section: Discussionmentioning
confidence: 99%